Artificial Intelligence in Operational Communication: Analysis of AI Use in Organizational Communication Systems - Gulda Patria (Journal of Dialogos, 2026)
The proliferation of artificial intelligence (AI) technologies has fundamentally reshaped organizational communication systems, offering new possibilities for automating, augmenting, and optimizing information flows across all levels of organizational operation. This study analyzes the use of AI in organizational communication systems, with a focus on identifying the dimensions, applications, challenges, and strategic implications of AI integration in operational communication. Drawing on a systematic review of peer-reviewed literature published between 2021 and 2024, the study synthesizes findings from multidisciplinary fields including organizational behavior, information systems, operations management, and communication studies. The results indicate that AI applications in organizational communication span a broad spectrum, from natural language processing and intelligent decision-support systems to generative AI tools and predictive analytics. Key enabling factors include leadership commitment, organizational readiness, AI competency development, and trust formation. Critical challenges involve ethical concerns, algorithmic bias, data privacy, and workforce adaptation. The study proposes an Integrated AI Communication (IAC) Framework that maps the relationships between AI capabilities, communication processes, and organizational outcomes. Findings contribute both theoretical insights and practical guidelines for organizations seeking to harness AI for enhanced operational communication.